THE DEVELOPMENT OF FOLLICLES AND OOCYTES VIABILITY FROM EWE OVARIUM POST-INTRAUTERINE TRANSPLANTATION TO PSEUDOPREGNANT RABBIT - Sumarmin, Ramadhan; Winarto, Adi; Laswardi Yusuf, Tutty; Boediono, Arief (Jurnal Veteriner, 2008)
The objective of this study was to evaluate the development of ewe follicles and oocytes viabilityfollowing an intrauterine transplantation of the ovaries into pseudopregnant rabbit. The experiment wasconducted in day 1 of pseudopregnant rabbit. Following transplantation for 5, 7, and 9 days, the ovarieswere recollected. The development of follicles determined by counting the number of follicles in paraffinembedded ovaries after staining with haematoxylin-eosin (HE). The viability of oocytes was determined byslicing the ovaries. Oocytes were incubated in CO2 incubator with 5% CO2, 38°C for 24 hours. After maturation,the oocytes were stained with 2% aceto-orcein to determine the nuclear oocytes status. The result showedthat follicles were detected in all stages of their development (primordial, primary, preantral, and antralfollicle stages), but their number decreased significantly (P<0.05) 5, 7 or 9 days after transplantation,except for those at primordial stage which at day 5 post-transplantation (634.7±56.88) were not significantlydifferent to the control (683.7±61.55). After maturation, the oocytes that were able to reach the M-II phaseat day 5 and day 7 post-transplantation were 35.05% and 35.24% respectively. They were significantly(P<0.05) lower than the control (56.65%). In conclusion, the development of follicles and oocytes viability inthe ewe ovaries in pseudopregnant rabbits was still preserved during intrauterine transplantation.
Keywords: ovarium, follicles, oocytes, viability, post-intrauterine transplantation